Biodegradation of Low-Density Polyethylene—LDPE by the Lepidopteran Galleria Mellonella Reusing Beekeeping Waste - Poma, Orlando; Ricce, Betty; Beraún, Jeyson; Perez Carpio, Jackson Edgardo; Fernandez, Hugo; Soria, Juan (Frontiers in Bioengineering and Biotechnology, 2022)
Plastic pollution is one of the most serious environmental problems of this century, most of them are single-use, and once their useful life is over, they become polluting, since their decomposition takes approximately 100 to 400 years. The objective of this research is to evaluate the efficacy of low-density polyethylene (LDPE) biodegradation by Galleria mellonella in the district of Pangoa, Junín, Peru. For the development of the study, the Galleria mellonella was conditioned in three groups of beekeeping residues (beeswax, balanced diet and wheat bran), after the conditioning stage the biodegradation treatment was developed, which consisted of placing the Galleria mellonella in terrariums with the LDPE, the treatments were carried out at three different times (24, 36 and 48 hours). To evaluate the efficacy of biodegradation, two analyzes were taken into account: the RAMAN analysis of the LDPE samples and the weight reduction of the treated LDPE. The results of the RAMAN analysis indicated that the best treatment was the one applied with Galleria mellonella conditioned with beeswax, obtaining a wavelength intensity of 0.45 µ.a., while the weight reduction of the PEBD indicated that the best results they were given at 36 hours and conditioned with beeswax with a reduction of 236.3 mg. In conclusion, the use of Galleria mellonella for the biodegradation of LDPE is effective when it is conditioned with beeswax and the treatment is carried out at 36 hours